Gender Transformative Approaches to Strengthen Women’s Land and Resource Rights - Morgan, M.; Larson, A.M.; Trautman, S.; Garner, E.; Elias, M.; Meinzen-Dick, Ruth S. (2023)
International standards and policies are clear about women’s right to equality in the enjoyment of all their rights, including rights to access, use, inherit, control and own land. Sustainable Development Goal Target 5.a specifically calls for reforms to give women equal rights to economic resources, as well as access to, ownership and control over land and natural resources. Securing women’s land and resource rights is a critical goal in and of itself - and also a crucial factor in achieving many of the other SDGs.